2015
DOI: 10.1038/ncomms8458
|View full text |Cite
|
Sign up to set email alerts
|

Non-redundant requirement for CXCR3 signalling during tumoricidal T-cell trafficking across tumour vascular checkpoints

Abstract: T cell trafficking at vascular sites has emerged as a key step in antitumor immunity. Chemokines are credited with guiding the multistep recruitment of CD8+ T cells across tumor vessels. However, the multiplicity of chemokines within tumors has obscured the contributions of individual chemokine receptor/chemokine pairs to this process. Moreover, recent studies have challenged whether T cells require chemokine receptor signaling at effector sites. Here, we investigate the hierarchy of chemokine receptor require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
336
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(389 citation statements)
references
References 69 publications
29
336
4
1
Order By: Relevance
“…The basis for such negative binding cooperativity was not determined but was suggested to be a consequence of allosteric modulation across the receptor heteromer interface. Although there is no evidence that CCR2 or CCR5 mediate the intratumoral accumulation of T cells, and, in fact, there is a report that CCR5 does not mediate this process (Mikucki et al 2015), these findings do show the capacity of CXCL12 to cause CXCR4 to suppress the signaling by another chemokine receptor. In this respect, then, it may be relevant that CXCR4 and CXCR3 have been shown to form heteromeric complexes when ectopically expressed in HEK293T cells (Watts et al 2013).…”
Section: Cxcr4 As the Chemokine Receptor That Inhibits Cxcr3mentioning
confidence: 81%
See 2 more Smart Citations
“…The basis for such negative binding cooperativity was not determined but was suggested to be a consequence of allosteric modulation across the receptor heteromer interface. Although there is no evidence that CCR2 or CCR5 mediate the intratumoral accumulation of T cells, and, in fact, there is a report that CCR5 does not mediate this process (Mikucki et al 2015), these findings do show the capacity of CXCL12 to cause CXCR4 to suppress the signaling by another chemokine receptor. In this respect, then, it may be relevant that CXCR4 and CXCR3 have been shown to form heteromeric complexes when ectopically expressed in HEK293T cells (Watts et al 2013).…”
Section: Cxcr4 As the Chemokine Receptor That Inhibits Cxcr3mentioning
confidence: 81%
“…Within 24 h of treatment initiation, T cells had accumulated among cancer cells, and within 48 h, in combination with a T-cell checkpoint antagonist, anti-PD-L1 antibody, to which mouse and human PDACs are consistently resistant, the mouse tumor volume had decreased by 15%. If the many publications attesting to the inhibitory specificity of AMD3100 for CXCR4 are correct, and if this PDAC tumor model obeys the same, nonredundant requirement for CXCR3 expression and function by CD8 þ T cells in the B16 mouse melanoma (Mikucki et al 2015), one is led to the conclusion that CXCR4 signaling suppresses the intratumoral function of CXCR3 in mouse PDAC to mediate the exclusion of T cells. The finding that AMD3100 also led to immune control of an ectopic Lewis lung tumor expressing the antigen, ovalbumin (Feig et al 2013), indicates that this conclusion is not restricted to mouse PDAC.…”
Section: Cxcr4 As the Chemokine Receptor That Inhibits Cxcr3mentioning
confidence: 98%
See 1 more Smart Citation
“…29 Mouse models investigating the mode of action suggests that CXCR3 is crucial for the firm adhesion of rolling T cells and transmigration across the vascular endothelium. 31 As both CCR5 and CXCR3 are highly expressed on in vitro activated and expanded TILs, trying to augment expression of these in a therapeutic setting is of little relevance. One might instead speculate whether it is possible to boost tumor secretion of the respective ligands, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…High numbers of TILs correlate with increased expression of multiple chemokines capable of recruiting effector T cells, including CCL2, CCL3, CCL4, CCL5, CXCL9, and CXCL10 [23]. Recent work has indicated that the most critical chemokines of them are CXCL9 and CXCL10, which are recognized by CXCR3 on effector CD8 + T cells [24]. Interestingly, recent mouse model data has indicated that the major source of these chemokines is the subset of dendritic cells (DCs) characterized by the basic leucine zipper transcription factor ATF-like 3 (Batf3), which in the mouse express surface CD103 or CD8α.…”
Section: Introductionmentioning
confidence: 99%